Traffic impact assessment of new commercial developments in the neighborhoods of Skudai town - Zaki, Nazir Huzairy (2013)
Urban areas in Malaysia including Johor Bahru are witnessing a rampant commercial development. The purpose of development can easily be defeated by unanticipated traffic congestion and other negative impacts. This paper deals with traffic impact assessment (TIA) of proposed commercial development in the neighbourhoods of Skudai Town. In traffic impact studies, estimation of mean trip rate is a central component for TIA and adoption of inaccurate trip rates can result into underestimation or overestimation of development traffic, both with undesirable impacts. This paper analyses three regimes of Trip Rate Analysis, Cross- Classification Analysis and Regression Analysis techniques to determine the future development traffic for a proposed Tesco hypermarket (TH) within Skudai Town. Furthermore, the obtained mean trip rates for critically examined for their adoption and forecasting traffic for base year 2015 and horizon year 2025. The results indicated significant variances in the estimated entry mean trip rates when compared with the entry trip rates from Trip Generation Manual (TGM) Malaysia. These estimated mean trip rates were then tested to measure the performance of critical intersection in the immediate vicinity of proposed Tesco Hypermarket for the opening year 2015. Critical Intersection is analysed using SIDRA software to estimate delay, a criterion for determining the level of service (LOS) provided to motorists. The traffic projections made for horizon year 2025 were further analysed, depicting a LOS F with 2716.9s of average delay. Furthermore, traffic improvements were proposed to mitigate the impact of future development traffic. In this regard, the study provided a framework for the estimation of trip rates for local Malaysian conditions and their adoption guidelines. These offer indispensible assistance to TIA that can assist developers or local authorities in decision making.